Completion pancreatectomy after pancreatoduodenectomy: who needs it? - Loos, Martin; König, Anna-Katharina; von Winkler, Nikolai; Mehrabi, Arianeb; Berchtold, Christoph; Müller, Beat P.; Schneider, Martin; Hoffmann, Katrin; Kulu, Yakup; Feißt, Manuel; Hinz, Ulf; Lang, Matthias; et al. (Annals of surgery, 2023)
Objective: - The objective of this study was to identify the indications for and report the outcomes of completion pancreatectomy (CPLP) in the postoperative course after pancreatoduodenectomy (PD). - Background: - CPLP may be considered or even inevitable for damage control after PD. - Methods: - A prospectively maintained database of all patients undergoing PD between 2001 and 2019 was searched for patients who underwent CPLP in the postoperative course after PD. Baseline characteristics, perioperative details, and outcomes of CPLP patients were analyzed and specific indications for CPLP were identified. - Results: - A total of 3953 consecutive patients underwent PD during the observation period. CPLP was performed in 120 patients (3%) after a median of 10 days following PD. The main indications for CPLP included postpancreatectomy acute necrotizing pancreatitis [n=47 (39%)] and postoperative pancreatic fistula complicated by hemorrhage [n=41 (34%)] or associated with uncontrollable leakage of the pancreatoenteric anastomosis [n=23 (19%)]. The overall 90-day mortality rate of all 3953 patients was 3.5% and 37% for patients undergoing CPLP. - Conclusions: - Our finding that only very few patients (3%) need CPLP suggests that conservative, interventional, and organ-preserving surgical measures are the mainstay of complication management after PD. Postpancreatectomy acute necrotizing pancreatitis, uncontrollable postoperative pancreatic fistula, and fistula-associated hemorrhage are highly dangerous and represent the main indications for CPLP after PD.